2022
DOI: 10.1038/s41598-022-23764-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural informatic study of determined and AlphaFold2 predicted molecular structures of 13 human solute carrier transporters and their water-soluble QTY variants

Abstract: Solute carrier transporters are integral membrane proteins, and are important for diverse cellular nutrient transports, metabolism, energy demand, and other vital biological activities. They have recently been implicated in pancreatic cancer and other cancer metastasis, angiogenesis, programmed cell death and proliferation, cell metabolism and chemo-sensitivity. Here we report the study of 13 human solute carrier membrane transporters using the highly accurate AlphaFold2 predictions of 3D protein structures. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In previous work, we used AlphaFold2 to predict the structures of water-soluble QTY variants of G protein-coupled receptors [ 15 ], glucose transporters [ 16 ], s olute c arrier t ransporters (SLC) [ 17 ], and potassium ion channels [ 18 ]. These predictions were in agreement with previously known experimentally-determined structures obtained through X-ray crystallography or cryo-EM methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we used AlphaFold2 to predict the structures of water-soluble QTY variants of G protein-coupled receptors [ 15 ], glucose transporters [ 16 ], s olute c arrier t ransporters (SLC) [ 17 ], and potassium ion channels [ 18 ]. These predictions were in agreement with previously known experimentally-determined structures obtained through X-ray crystallography or cryo-EM methods.…”
Section: Resultsmentioning
confidence: 99%
“…The expressed and purified water-soluble variants exhibited the predicted characteristics and maintained their ligand-binding activity [9][10][11][12][13][14]. After the Alpha-Fold2 was released in July 2021, we immediately used AlphaFold2 to make QTY variant protein structure predictions and achieved improved results in less than an hour [15][16][17][18], compared to the previous method which took approximately 5 weeks per simulation [9][10][11]. Additionally, we developed a program and website for designing water-soluble QTY variants of membrane proteins [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the CryoEM structures were determined experimentally by different research groups, we asked how well would the structures superpose with the AlphaFold2-predicted native structures and their water-soluble QTY variants, as we did in our previous studies (Skuhersky et al, 2021 ; Smorodina et al, 2022a , b ). We thus superposed the AlphaFold2-predicted native structures and their water-soluble QTY variants ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…These water-soluble variants were then used to elucidate the mechanism of native receptor-ligand interaction and their binding abilities despite significant truncation in several chemokine receptors (Qing et al, 2019 , 2020 ). Using the online version of AlphaFold2, we predicted the QTY variant structures of 7 chemokine receptors and 1 olfactory receptor (Skuhersky et al, 2021 ), 14 glucose transporters (Smorodina et al, 2022a ), and 13 solute carrier transporters (Smorodina et al, 2022b ). We recently also showed that the QTY code also works very well for bacterial outer membrane beta-barrels (Sajeev-Sheeja et al, 2023 ) and for IgG antibodies that are rich in beta-sheet structures (Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The water‐solubilization design by QTY code produced detergent‐free transmembrane receptors that retained ligand‐binding affinity 21–23,25 and high thermostability. Structural informatic studies using the highly accurate machine learning‐based structure prediction approach AlphaFold2 26 (AF2) showed the significant superpositions between the native proteins and their QTY variants 27–30 . This general QTY code could have far‐reaching implications for designing protein water‐solubility, opening the door to designing proteins for a wide range of applications for pharmaceutically therapeutic mAbs, protein, and peptide‐based biologics that can treat a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%